Prinsip Ockham dan Teorema Ketidaklengkapan Gödel dalam Pembuktian Keberadaan Dan Ketidakberadaan : Ockham's Principle and Gödel's Incompleteness Theorems in Proving Existence and Non-Existence - Putawa, Rilliandi Arindra (Jurnal Filsafat Indonesia, 2025)
This study aims to explore the views of William Ockham and Kurt Gödel regarding the concepts of being and non-being in relation to the interplay between science and religion. Using a comparative method with a philosophical approach, the study analyzes the contributions of Ockham's Razor principle and Gödel's Incompleteness Theorem to metaphysical discussions. The findings reveal that both thinkers advocate minimizing non-empirical assumptions in scientific explanations to maintain simplicity and consistency. The implications of this study indicate that the involvement of supernatural entities in scientific explanations can lead to inconsistencies and a loss of scientific essence. The conclusions emphasize the importance of epistemological boundaries in integrating science and religion.